Domestic Investment Laws and State Capitalism. Issue 1 (February 2023) - Qian, Xu
Abstract: State capitalism and the liberal economic order have had an antagonistic relationship. While the international economic law rules have sought to reduce the role of the state in the economy, state-controlled entities have more recently increased in size and importance – both domestically, as well as internationally. In this connection, the article analyses the effects of state capitalism's expansion simultaneously with the domestic investment law of States. The article analyses the underlying principles of state capitalism in an effort to answer the question of whether domestic laws promoting investment – as defined in the special issue – are positive, negative, or neutral to state capitalists. The article further interprets the trends spawned by the propagation of the liberal international economic order as states realize their development targets and envisage to actively contribute to the regulation of international trade and cross-border transactions globally.